A NEED ANALYSIS OF ENGLISH HYBRID LEARNING USING OPEN BROADCASTER SOFTWARE (OBS) THROUGH PROJECT-BASED LEARNING (PJBL) MODEL TO PRIMARY SCHOOL STUDENTS - Pandesha, Freshy Loisan; Roharjo, Makmum; Mirizon, Soni (English Review: Journal of English Education, 2023)
This study aimed to determine the need for English hybrid learning using the Open Broadcaster Studio (OBS) through Project Based Learning (PjBL) Model. This research applied research and development (R&D) approach. The development model used was ASSURE model.  Preliminary study conducted on 37 respondents consisting of 12 teachers and 25 students of primary school at RSI Indonesia School. The results of the study showed that the need for English hybrid learning is very necessary to overcome problems found during the learning process. Teachers need teaching model that can support the learning process and provide solutions if students experience obstacles during learning.  The results of the research at the needs analysis showed that there were obstacles in the implementation of online learning that need to be solved. A learning model that can solve problems occurred in online learning, and also has a systematic learning stages to make students participate actively in learning process and to produce a project that can improve students' creative thinking is crucially needed. This study provides an overview and direction to teachers to continue developing effective hybrid learning and become a resource for further research in hybrid learning model development.